Perancangan Media Poster Sebagai Sarana Informasi dan Promosi Website 3:30 Kopi Berbasis Metode Design Thinking - Destiani, Fajrin; Gupita Cinantya, Ixsora (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The design of the 3:30 Kopi website poster was carried out as an effort to present an effective and modern promotional medium to support information needs and introduce the café’s digital platform to the wider community. In line with the development of the digital era, local SMEs such as 3:30 Kopi are required to remain competitive by utilizing visual media that is both communicative and appealing. This poster functions not only as an information tool but also as a branding strategy to strengthen the café’s identity in the eyes of consumers, particularly in the Ciledug area and its surroundings. The visual concept of the poster was designed with careful consideration of both aesthetics and function. The use of brown and cream tones symbolizes the warm and natural character of coffee, while also creating a friendly and elegant impression. Typography was chosen with a simple yet bold style to ensure information is easy to understand. The main elements, featuring a mockup of the website displayed on both laptop and mobile devices, emphasize the flexibility and responsiveness of the platform, which can be accessed anytime and anywhere. In addition, the inclusion of a QR code provides a modern solution that facilitates quick and practical interaction between the audience and the website. Cultural-inspired ornaments derived from 3:30 Kopi’s signature menu further reinforce its visual identity while adding aesthetic value. Through this poster design, 3:30 Kopi is expected to increase brand awareness, attract new visitors, and strengthen its image as a café that not only offers coffee but also provides a productive social space suited to the needs of modern society.